Macroeconomic inequality from Reagan to Trump : market power, wage repression, asset price inflation, and industrial decline - Taylor, Lance, 1940- (Cambridge : Cambridge University Press, 2020)
For five decades, rising US income and wealth inequality has been driven by wage repression and production realignments benefitting the top one percent of households. In this inaugural book for Cambridge Studies in New Economic Thinking, Professor Lance Taylor takes an innovative approach to measuring inequality, providing the first and only full integration of distributional and macro level data for the US. While work by Thomas Piketty and colleagues pursues integration from the income side, Professor Taylor uses data of distributions by size of income and wealth combined with the cost and demand sides, flows of funds, and full balance sheet accounting of real capital and financial claims. This blends measures of inequality with national income and product accounts to show the relationship between productivity and wages at the industry sector level. Taylor assesses the scope and nature of various interventions to reduce income and wealth inequalities using his simulation model, disentangling wage growth and productivity while challenging mainstream models.
Title from publisher's bibliographic system (viewed on 17 Jul 2020).
Keywords: Income distribution -- United States -- History -- 20th century; Income distribution -- United States -- History -- 21st century; Macroeconomics -- United States -- History -- 20th century; Macroeconomics -- United States -- History -- 21st century; United States -- Economic conditions -- 1945-